Manajemen Perencanaan Rekrutmen Pesrta Didik Dipondok Pasantren Busra Khalid - Bambang Bambang (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
This research was conducted at the Busra Khalid Islamic Boarding School with the aim of describing the student planning management that it carries out. The research method used is qualitative with data collection techniques through interviews, observation and documentation. The research results showed that student planning management was carried out starting from an analysis of student needs based on the number of registrants from the previous year, student recruitment planning by forming a committee and disseminating information using a formal approach, selection planning which was carried out by involving prayer tests and reading the Al-Qur' and involving the Islamic boarding school, orientation planning is carried out jointly by introducing the school and Islamic boarding school environment, planning different placements between classes, as well as recording and reporting using master books, attendance attendance and student achievement records. The planning management of students at the Busra Khalid Islamic Boarding School can be said to be ideal according to existing theory and regulations and in several stages of student planning there are characteristics of Islamic boarding schools that are inserted.